A Comparative Analysis of Churna and Ksheerapaka of Dried Root of Prishniparni- Desmodium Gangeticum (Linn.) DC. through High Performance Thin Layer Chromatography. - Aswathy , Krishna R; Ansary, P Y; Oommen, Sara Monsy; Shincymol , V V (International Research Journal of Ayurveda & Yoga, 2022)
High Performance thin layer chromatography has become a potent analytical technique in the process of drug discovery. It serves as a tool for identification, authentication and quality control of herbal drugs due to its reliability and simplicity. Prishniparni -Desmodium gangeticum (Linn.) DC. is a significant and well-known drug expoundly discussed in the Ayurvedic classics. It is an erect diffusely branched undershrub with enriched therapeutic potential. The plant root is rich in flavonoids, iso flavonoids, cardiac glycosides, pterocarpans, alkaloids and steroids which accounts for its multiple beneficial action in the therapeutics. It has strong antioxidant and cardioprotective properties. The churna (powder) and ksheerapaka (milk decoction) of dried root of Prishniparni was subjected to High Performance thin layer chromatography and comparative analysis of different peaks were obtained. The results suggest that change in phytochemical constituents and their quantity occur on changing the Kalpana (dosage form) from churna (powder) to ksheerapaka (milk decoction).